(untitled) (Bangladesh Veterinarian, 2017)
Brucellosis is an important contagious bacterial disease of livestock, which can be transmitted to humans. It is prevalent in many countries including India. Vaccination and biosecurity can reduce the prevalence of brucellosis. Evaluation of immune response of live Brucella abortus vaccine containing S19 strain in 10 calves was studied, with 10 unvaccinated controls. The percentage inhibition (PI) values (78.0 ± 4.9) were positive from one month after vaccination and the protection was sustained up to six months after vaccination. Rose Bengal Test (RBT) values were positive in 9/10 calves until 10 months after vaccination. Bangl. vet. 2016. Vol. 33, No. 1, 28-32